Values of Moral Education in the Qur'an Suroh Ali Imran Verse 134 - Laila Auni; Nur Azizah Nasution; Alimuddin Siregar (Edumaspul: Jurnal Pendidikan, 2024)
The background to this research is the widespread decline in morals found in various circles, both with oneself and with others. This happens due to a lack of knowledge which becomes the source of reason and spiritual input, namely advice and others, even because of following one's own desires, so that morals are not controlled and become the main problems that arise among society, such as greed , difficulty controlling emotions and selfishness, making it difficult to create other good deeds. Starting from this, the author was interested in studying more deeply the values of moral education contained in the QS. Ali Imran verse 134. This aims to find out the moral values contained in the QS. Ali Imran verse 134, so that you can increase your knowledge and efforts in implementing the message and commands of Allah SWT. This research is library research whose data was obtained from two sources. The first primary source is QS. Ali Imran verse 134. The two secondary sources are in the form of commentary books, books, articles and others that support this research. The method used is the Maudhu'i method with qualitative analysis and then reprocessed using deductive, inductive and comparative methods. The results of the research show that: 1) give to each other under any circumstances. 2) restrain emotions. 3) forgive other people's mistakes. 4) do good to people who have wronged them and this is the pinnacle of the nobility of a servant's morals and devotion.